Pengaruh Terapi Spiritual Bimbingan Do’a Terhadap Tingkat Kecemasan Pasien Pre Opersi Dengan Spinal Anestesi - Suyanto Suyanto; Indri Indri; Farid Taufiqurrahman (Jurnal Ilmu Kesehatan dan Gizi, 2023)
Background: Surgery or surgery that has been planned can bring about a stress reaction in patients, both physiological and psychological stress. The occurrence of this stress can lead to a condition of preoperative patient anxiety. Planned surgical actions can cause physiological and psychological responses in patients. The psychological response that usually occurs in preoperative patients is anxiety. Research Objectives: Knowing the effect of giving spiritual therapy guided by prayer on the level of anxiety in preoperative patients with spinal anesthesia in Jombang Hospital. Research Methods: This type of research uses a quasi experimental method with a pre post test research design with a control group design. Respondents were given pretest and posttest treatment using the APAIS scale measurement. The sample in this study was 22 respondents in the intervention group and 22 respondents in the control group. The sampling technique used consecutive sampling technique. Data collection was carried out in November - June 2021. Research Results: The results of data collection were processed using the Wilcoxon test in the intervention group of 0.000 and in the control group of 0.014 and using the Mann Whitney test. Results The Mann Whitney test yielded p=0.006 (p<0.05), so Ha was accepted. Conclusion: There is a significant effect of prayer guidance therapy on the anxiety level of preoperative patients with spinal anesthesia.